Informal credit constraints and farmers’ health: an empirical study of China - Dong,Xinyue (2021)
ABSTRACT: Based on survey data of the income distribution and living conditions of urban and rural residents collected by the China Economic Monitoring and Analysis Center in 2014, we investigated the mechanisms related to informal credit constraints on farmer health and then empirically analyzed the impacts of such constraints. Results showed that, in general, informal credit constraints significantly negatively impact farmer health. Compared with farmers whose credit was not informally constrained, the probability of farmers who faced informal credit constraints describing their self-rated health as “very good” fell by 6.64%. After controlling for endogenous problems, this proportion rose to 28.87%. Correspondingly, the probability of describing self-rated health as “very bad” increased by 0.45%. After controlling for endogenous problems, this proportion rose to 0.81%. The robustness test showed that our conclusions are strongly robust. Informal credit constraints significantly positively impacted the number of days of illness in 2013 in the sample of farmers, which means farmers who suffered from informal credit constraints required more sick days than those who did not experience informal credit constraints in 2013. As far as we know, this is the first study on the impact of informal credit constraints on Chinese farmer health.